PENINGKATAN KREATIVITAS SENI DALAM DESAIN BUSANA - Nanie Asri Yuliati (FBS UNY, 2007)
Creativity in cloth designing is one of aspects to improve fashion products. The products in garment industry include many kinds of clothes in the markets, such as women's, men's, children's and adults' clothes for many occasions like parties' and work's clothes. To compete in the markets, fashion designers have to be creative in designing the clothes. Creativity is new ideas in designing to create novel designs and products suitable with the current trends. To trigger creativity in the learning of fashion design, the role of learning sources is important so that the students get inspired by the novelties to create new fashion. The learning sources include electronic media (TV, video and the internet), printed media (fashion books and magazines, tabloids, and newspapers) as well as direct sources observed in daily life. Varied learning sources will improve creativity in fashion design learning. Key words: learning sources, creativity, cloth design